1990
DOI: 10.1111/j.1365-2672.1990.tb01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quantitative and qualitative methods of detecting hydrogen peroxide produced by human vaginal strains of lactobacilli

Abstract: A quantitative method was developed for the measurement of micromolar quantities of H2O2 produced in Rogosa broth and peptonized milk broth by vaginal strains of lactobacilli isolated from women. The production of substantial amounts reproducibly was dependent on the growth of the organisms in acid media (pH less than or equal to 6.0) under anaerobic or micro-aerophilic conditions with continuous agitation. The addition to the media of the enzyme inhibitor, 3-amino-1,2,4-triazole, with or without catalase some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…It is not clear whether production is constitutive or inducible or the extent of dependence on phase of growth, medium constituents, and redox potential. Shaken aerobic cultures may result in higher levels of H 2 O 2 production than anaerobic cultures (11,33). Vallor et al found isolates of L. crispatus and L. jensenii that did not produce H 2 O 2 , whereas all of our isolates of these species did produce H 2 O 2 .…”
Section: The Most Common Vaginal Species In This and Other Studies Armentioning
confidence: 46%
“…It is not clear whether production is constitutive or inducible or the extent of dependence on phase of growth, medium constituents, and redox potential. Shaken aerobic cultures may result in higher levels of H 2 O 2 production than anaerobic cultures (11,33). Vallor et al found isolates of L. crispatus and L. jensenii that did not produce H 2 O 2 , whereas all of our isolates of these species did produce H 2 O 2 .…”
Section: The Most Common Vaginal Species In This and Other Studies Armentioning
confidence: 46%
“…Additionally, the activity of H 2 O 2 is influenced by the hydrogen ion concentration in the environment. Hydrogen peroxide is stable under acidic conditions and is degraded as the hydrogen ion concentration decreases (26).…”
Section: Discussionmentioning
confidence: 99%
“…In general, more catalase was required to neutralize the inhibition by all lactobacilli as the pH of the base agar decreased (pH 7.6, 7.0, 6.6, 6.3, and 5.8) (data not shown). This observation may be explained by increased production of H 2 O 2 by lactobacilli at low pH or increased stability of H 2 O 2 at low pH (5).…”
mentioning
confidence: 99%